Synovial Sarcoma of Retropharyngeal space Presenting as Caries Spine - Khan, Amjad; Zaman, Javed; Ahmad, Iftikhar; Jan, Abdullah (Journal of Postgraduate Medical Institute, 2011)
Synovial Sarcomas are uncommon soft tisue tumours which occur in the region of joints but never involve them. The great majority occurs in patients between the age of 15 and 35 years but older and younger persons may be affected.f Themale to feamle ratio is approximately 1.5:1. histologically these are mainly biphasic tumours having distinct epithelial and well - defined spindle cell components. In more than half of the cases, these patients present with a tender or painful deep - seated mass in close proximity to the bone or joints. Radiographs may sometimes show erosion or even invasion of adjacent bone. Metastates are rare in slow growing tumours but some tumours are rapidly enalrging and present with metastatses to the lungs. The treatemnt depends upon the site and extent of the disease. neoplasms of areas where surgical access is not possible or carries high risk, adjuvant therapy consisting of radiotherapy and chemotherapy is the treatment of choice.